2013
DOI: 10.2337/dc12-1712
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset, Coexisting Autoimmunity and Decreased HLA-Mediated Susceptibility Are the Characteristics of Diabetes in Down Syndrome

Abstract: OBJECTIVEdDown syndrome (DS) is associated with an increased risk of diabetes, particularly in young children. HLA-mediated risk is however decreased in children with DS and diabetes (DSD). We hypothesized that early-onset diabetes in children with DS is etiologically different from autoimmune diabetes.RESEARCH DESIGN AND METHODSdClinical and immunogenetic markers of autoimmune diabetes were studied in 136 individuals with DSD and compared with 194 age-and sex-matched individuals with type 1 diabetes, 222 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 37 publications
4
41
0
Order By: Relevance
“…A previous study showed that DS with diabetes had intermediate HLA association (7). The highest-risk HLA diplotype-DR3/DR4-was present in half as many DS diabetes cases compared with T1D (17% of DS diabetes, 38% of T1D, 3% of control subjects).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A previous study showed that DS with diabetes had intermediate HLA association (7). The highest-risk HLA diplotype-DR3/DR4-was present in half as many DS diabetes cases compared with T1D (17% of DS diabetes, 38% of T1D, 3% of control subjects).…”
Section: Discussionmentioning
confidence: 90%
“…Large studies have shown childhood-onset autoimmune diabetes is four times more common in DS than in the general population and has an intermediate HLA association (6). There have been three reported cases of DS with diabetes diagnosed before 6 months (DS-PNDM) (7,8). However, it is not known whether DS was the cause of PNDM or a coincidental finding in these patients.…”
mentioning
confidence: 99%
“…Although conditions such as autoimmune disease are common in people with DS, there is a lack of studies exploring the relationship of these conditions with thyroid disease. One study noted a prevalence of thyroid disease in 74% of a sample of 136 children with diabetes and DS (Aitken et al, ), but studies about the co‐occurrence of thyroid disease and other autoimmune conditions in adults are limited (Prasher, ).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of an extra copy of chromosome 21 in the DS genome puts DS individuals at high risk for developing certain comorbidities, such as AD, immune dysfunction, diabetes and leukemia (1,4,6,7,(84)(85)(86). Many of the DS comorbidities are associated with a dysfunctional PN (14-21) and aneuploidy has also been associated with proteotoxic stress and PN dysfunction (43)(44)(45)(46)(47)(48)(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…Down syndrome (DS) is a genetic condition originating from the presence of a third copy of chromosome 21 (Tri21) (1) and is the only known trisomy that does not result in early life lethality (2). DS is characterized by a variable phenotype with several comorbidities, including Alzheimer's disease (AD) (1), cognitive disabilities (3), diabetes (4), and leukemia (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%